Studi Komparasi Survei Kepuasan Masyarakat (SKM) Terhadap Pelayanan Publik Tahun 2019 (Studi di Dinas Dukcapil Kota Mataram dan Dukcapil Kabupaten Lombok Barat) - hidayat, rahmad hidayat; Rahcman, M. Taufik; Burhan, M. Rahmatul (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2020)
Public services that should have been better in every country, in every province and even in every region to the villages, but apparently our minds still see and lead to a complicated and complex public service process. This shows that the condition of public services in Indonesia is still far from the expectations of the community. As for the formulation of the problem in this study, namely: How do the comparisons / comparisons of the Community Satisfaction Survey (SKM) Against Public Services in 2019 (Study at the Mataram City Dukcapil and Dukcapil Services in West Lombok Regency)? and what are the inhibiting and supporting factors in public services conducted by the Mataram City Dukcapil Office and West Lombok Dukcapil District ?. This research is a type of survey research. Based on the results of the study note the comparison / comparison of the Community Satisfaction Survey (SKM) on Public Services in 2019 in the West Lombok Regency Dukcapil and Mataram City Dukcapil Services obtained the value of service quality with the category